Assembly of the executive mind evolutionary insights and a paradigm for brain health - Hoffmann, Michael W. (Cambridge University Press, 2019)
Over 90% of the brain is concerned with higher cortical functions, yet understanding of syndromes, functions, and measurements remains unchartered. This valuable handbook illuminates brain function, natural environment and human function, by delving into the interdisciplinary study. Multifaceted in its perspective, this book demonstrates bi-directionality of information exchange between disciplines. This book weaves around key case reports, series, control studies and cohort studies from cognitive neurology registries, to present the most current, practical research. Gaining appreciation for the fundamental formation and assembly of the supervisory area of the brain will inform an understanding of conditions and behavior for neuroscience professionals, clinical brain scientists and medical students in neuroscience, worldwide. Authored by a leading expert in cognitive neurology, this book guides the reader through the evolutionary, or neuro-archeological, aspects of how the frontal lobes and their circuitry were assembled, drawing key insights into form, function and treatment.